Humanistic education in new social and cultural conditions - Filonenko, L. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article deals with the socio-cultural approach, which defines the strategy of youth’s interpersonal relationships development based on the principles of tolerance education, humanistic and universal values. In the times of social instability and spiritual crisis the formation of the youth humanistic values has become an urgent educational problem. Being the interaction mechanisms between an individual and the society, these values motivate human activity; determine both the nature of relationships in the society and human behavior. It is important for young people not to cross the border of humaneness and neglect humanistic principles. The ways to improve the efficiency of humanistic education are connected with the formalism overcoming (which is possible due to unsystematic approach, elimination of unwanted pupils’ engagement with too much activities), improving the educational activities of the teaching staff, creating a favourable moral-psychological climate at the educational establishment, the correct choice of the educational curricular according to the purpose and level of education of all participants of the educational process, etc. The article presents an analysis of topical problems dealing with the formation of modern Ukrainian youth’s humanistic value orientations. It determines the importance of humanistic value orientations in young people’s lives, i.e. in the choice of a future profession, attitude to their parents, friends and other people.